(untitled) (Annals of Medical Research, 2022)
Aim: Identifying patients with FD during the prenatal period or during delivery will help us intervene early. Therefore, we aimed at evaluating the maternal IMA status in pregnancies complicated by FD and comparing the results with those of healthy pregnancies. Materials and Methods: One hundred and twenty patients beyond the 34th week of pregnancy were included in the study, and they were divided into two groups. Group 1 (study group) included 60 patients who were diagnosed with fetal distress had to have a cesarean section due to the Fetal distress indication according to the NST; group 2 (control group) comprised 60 patients who showed no signs of Fetal distress or any other disease and had an elective C/S due to previous C/S. Results: There was no significant difference between the groups in terms of BMI, birth weight, maternal age, gravidity and parity. IMA concentrations were found to be lower in group 2 patients compared with group 1 patients (p < 0.001). Conclusion: Increased maternal IMA levels in the intrauterine fetal distress justify the need for maternal follow-up with IMA. Although studies on the value of IMA are still few in its use in perinatology practice, we think that more studies should be done in this field